2023
DOI: 10.1126/sciadv.adh0069
|View full text |Cite
|
Sign up to set email alerts
|

Structural pseudocapacitors with reinforced interfaces to increase multifunctional efficiency

Lulu Yao,
Kai Zheng,
Nandu Koripally
et al.

Abstract: Structural supercapacitors hold promise to expand the energy capacity of a system by integrating load-bearing and energy-storage functions in a multifunctional structure, resulting in weight savings and safety improvements. Here, we develop strategies based on interfacial engineering to advance multifunctional efficiency. The structural electrodes were reinforced by coating carbon-fiber weaves with a uniquely stable conjugated redox polymer and reduced graphene oxide that raised pseudocapacitive capacitance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The first carbon fiber (CF)-based structural capacitor was built in 2001 [9]; however, the term "SSCs" was first introduced by the United States Army in 2008 [10], but similar ideas on multifunctional materials have been circulated since at least 2003, as investigated by Christodoulou and Venables [11]. Currently, initial concept studies have been demonstrated for fuselage beams [12], satellite panels [13], and composite boat hulls [14] (Figure 1b-d). One of the first studies on the mechanical and electrical behavior of CF structural capacitors including the effects of delamination and interlaminar damage was conducted by Shen and Hongyu in 2017 [15] and prediction of the mechanical behavior of SSCs was carried out by Valkova et al in 2022 [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first carbon fiber (CF)-based structural capacitor was built in 2001 [9]; however, the term "SSCs" was first introduced by the United States Army in 2008 [10], but similar ideas on multifunctional materials have been circulated since at least 2003, as investigated by Christodoulou and Venables [11]. Currently, initial concept studies have been demonstrated for fuselage beams [12], satellite panels [13], and composite boat hulls [14] (Figure 1b-d). One of the first studies on the mechanical and electrical behavior of CF structural capacitors including the effects of delamination and interlaminar damage was conducted by Shen and Hongyu in 2017 [15] and prediction of the mechanical behavior of SSCs was carried out by Valkova et al in 2022 [16].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first studies on the mechanical and electrical behavior of CF structural capacitors including the effects of delamination and interlaminar damage was conducted by Shen and Hongyu in 2017 [15] and prediction of the mechanical behavior of SSCs was carried out by Valkova et al in 2022 [16]. [12], (c) multifunctional highly integrated satellite panel powered by structural supercapacitors [13], (d) boat hull with integrated structural supercapacitors [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation